Cell Migration Developmental Methods and Protocols - Guan, Jun-Lin.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2005)
Central to the better understanding of both molecular mechanisms and disease, cell migration plays an essential role in a variety of biological processes and is now the subject of intense study using an array of powerful new technologies. In Cell Migration: Developmental Methods and Protocols, researchers describe in step-by-step detail their most successful techniques for studying the macromolecular machinery of cell movement. These readily reproducible protocols include a wide range of novel and state-of-the-art methodologies, as well as many classic methods, for use in cultured cells, different model organisms, and specialized cells in both normal development and disease. Highlights include basic assays that apply to all cell migration studies in vitro, assays in various model organisms, and assays for cancer cells, endothelial cells, and neurons both in vitro and in animal models. The authors also offer several novel approaches to the study of cell migration, as well as extensive coverage of cell migration studies in developmental and disease models. The protocols follow the successful Methods in Molecular Biology™ series format, each offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and highly practical, Cell Migration: Developmental Methods and Protocols offers researchers easy access to many readily reproducible techniques for the optimally productive investigation of cell migration in today's interdisciplinary experimental environment.
Cell Migration -- Basic Cell Migration and Related Assays -- Boyden Chamber Assay -- Wound-Healing Assay -- Analysis of Cell Migration Using the Dunn Chemotaxis Chamber and Time-Lapse Microscopy -- Cell-Adhesion Assays -- Cell-Spreading Assays -- Cell-Scatter Assay -- Cell Migration Analyses Within Fibroblast-Derived 3-D Matrices -- Analysis of Cell Migration in Specialized Cell Systems -- Tumor Cell Invasion Assays -- Analysis of Endothelial Cell Migration Under Flow -- Angiogenesis Assays in the Chick CAM -- Investigations of Neuronal Migration in the Central Nervous System -- Analysis of Cell Migration in Model Organisms -- Analysis of Cell Migration in Caenorhabditis elegans -- Analysis of Cell Migration Using Drosophila as a Model System -- Imaging Cell Movement During Dorsal Closure in Drosophila Embryos -- Analysis of Cell Movements in Zebrafish Embryos -- The Xenopus Embryo as a Model System for Studies of Cell Migration -- Neural Crest Migration Methods in the Chicken Embryo -- In Vivo and In Vitro Models of Mammalian Angiogenesis -- Biochemical and Novel Approaches in Cell Migration -- Measurement of Protein Tyrosine Phosphorylation in Cell Adhesion -- Cell-Adhesion Assays -- Application of Microscope-Based FRET to Study Molecular Interactions in Focal Adhesions of Live Cells -- Use of Multiphoton Imaging for Studying Cell Migration in the Mouse -- Using Microfluidic Channel Networks to Generate Gradients for Studying Cell Migration.
Keywords: Cell biology; Cell Biology